Complete power distribution system representation and state determination for fault location (2015)
The impedance-based approaches for fault location in power distribution systems determine a faulted line section. Next, these require of the estimation of the voltages and currents at one or both section line ends to exactly determine the fault location. It is a challenge because in most of the power distribution systems, measurements are only available at the main substation.  This document presents a modeling proposal of the power distribution system and an easy implementation method to estimate the voltages and currents at the faulted line section, using the measurements at the main substation, the line, load, transformer parameters and other serial and shunt connected devices and the power system topology. The approach here proposed is tested using a fault locator based on superimposed components, where the distance estimation error is lower than 1.5% in all of the cases.